Mechanisms of the Chinese Government's efforts to fight COVID-19: integration of top-down interventions and local governance - Gao, Jinghua; Zhang, Pengfei (Health security, 2022)
The experiences and lessons of China's response to COVID-19 have been described in several studies, but the mechanisms of the Chinese government's efforts to fight COVID-19 have not been well characterized. Despite strong policy directives and orders from the central government, the response and handling of the epidemic also reflected distinctive characteristics of local governments in terms of their governance systems and capacities. In this article, we analyze public health policies and mechanisms of the Chinese government's response to COVID-19 based on the integration of top-down and local governance. A compendium of key events and measures provides the foundation for our analysis. Mechanisms related to leadership, emergency response, centralized mobilization, and accountability fully reflect the decisive measures for top-down interventions in the face of emergencies. China's policies and mechanisms to address the COVID-19 pandemic are consistent with its party-state bureaucracy and socioeconomic context. However, lower levels of government have used “repeated increments” and “one-size-fits-all” practices in the implementation of antiepidemic policies. Conservative local officials are more averse to social innovation and favor strict controls to manage the pandemic. Moreover, even under a unified system, there are substantial differences in the capacity and level of crisis management among local governments, especially in the mobilization of nonprofit organizations and volunteers. In this case study, we aim to expand the existing understanding of the tension between top-down interventions and local governance innovations.
Online veröffentlicht: 4. Juli 2022
Gesehen am 19.06.2023